2007
DOI: 10.1007/s10571-007-9223-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by 7-Nitroindazole Against Iron-Induced Hippocampal Neurotoxicity

Abstract: (1) Iron plays an important role in maintaining normal brain function. In some neurodegenerative disorders including Parkinson's and Alzheimer's disease, iron levels rise in the brain. It is known that higher iron levels induce neuronal hyperactivity and oxidative stress. A body of evidence indicates a relationship between neuronal death and nitric oxide (NO). The aim of present study was to evaluate the effects of NO produced by neuronal nitric oxide synthase (nNOS) on iron-induced neuronal death. (2) Animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The toxicity of DNIC's components seems to be mutually dependent on each other. 27,28 The presence of NO donors protects against iron-induced nephrotoxicity 29,30 or neurotoxicity, 31 whereas the inhibition of NO synthesis attenuates this effect. 32 In line with the attenuation of iron toxicity by NO, several studies revealed the ability of iron to rescue tumour cells from the anti-tumour activity of NO.…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of DNIC's components seems to be mutually dependent on each other. 27,28 The presence of NO donors protects against iron-induced nephrotoxicity 29,30 or neurotoxicity, 31 whereas the inhibition of NO synthesis attenuates this effect. 32 In line with the attenuation of iron toxicity by NO, several studies revealed the ability of iron to rescue tumour cells from the anti-tumour activity of NO.…”
Section: Introductionmentioning
confidence: 99%